THE EFFECT OF ADDING SURFACTANTS TO TOP COAT FINISHING ON THE APPEARANCE OF WHITE SPOT DEFECTS ON STEERING WHEEL LEATHER - Endah Oktaviyana; Nais Pinta Adetya; Emiliana Anggriyani (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2024)
The aim of this research is to determine the effect of using surfactant in the top coat layer on the appearance of white spot defects on the steering wheel leather. The appearance of white spot defects in the top coat layer is not expected because it disturbs the aesthetics of the skin and has the effect of uneven color on the skin surface, so the appearance of white spot defects must be prevented. The raw materials used in this research were 4 pieces of crust cowhide, with a thickness of 1.1-1.4 mm and an area of ​​1 sqft taken from 4 pieces of full hide leather. The main chemical used is non-ionic surfactant. The addition of non-ionic surfactant to the top coat layer was carried out with varying percentages of 0.5%, 1%, 1.5% and 2%. The tests carried out were organoleptic tests and physical tests. The results of the organoleptic test with the addition of 0.5% surfactant still showed white spot defects, whereas with the addition of 1%, 1.5% and 2% surfactant it met customer standards. The results of the physical test with the addition of 1% and 1.5% surfactant showed that the color fastness test did not fade, while with the addition of 2% the results obtained faded.